Promoting Interaction in Classroom via Bluetooth Mobile Messaging Feedback System (MMSF) - Cheak, Audrey Poh Choo (2006)
Interaction in the classroom has decreased unexpectedly in the recent years. This situation creates a serious threat to the learning environment because interaction plays an important role in shaping students' learning. Hence, an innovative approach is required to elicit student interaction in class. This research describes the use of Mobile Messaging Feedback System (MMFS), a client-server prototype system developed to pronounce interaction in class via mobile phone and Bluetooth technology. A set of design principles based on literature was employed to address the challenges to interaction and to build this prototype. This prototype was later experimented in a Java programming class, which was conducted in a computer lab at Informatics Institute. MMFS enables students to anonymously send questions using their mobile phones via Bluetooth to the lecturer's laptop. The lecturer sees the feedback in real time on her laptop and she can develop the interaction further by verbally addressing the feedback. The system is able to save all the students' feedbacks for a particular lesson into a database file for future review. The experiment, observation, interview and survey validate whether or not the students lecturer interaction could be increased with the usage of MMFS.